The Influence of Fear of Missing Out, Product Quality, and Social Proof on Cosmetic Product Purchase Decisions on TikTok - Yulia Lestari; Dian Oktarina; Thoyibatun Nisa (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: Purchasing decisions are influenced by various factors, including Fear of Missing Out (FOMO), product quality, and social proof. Previous research generally only examines the relationship between these two variables and focuses on specific markets or brands. However, research that simultaneously integrates these three variables in the context of cosmetic product purchases via TikTok is still limited. Therefore, this study aims to analyze the influence of FOMO, product quality, and social proof on cosmetic product purchasing decisions on TikTok. Methodology: This study used primary data obtained by distributing questionnaires to 100 respondents, using a 10% solution technique as the sampling method. The analysis technique used was multiple linear regression, with instrument testing, classical assumption testing, and hypothesis testing as requirements. Findings: The results of this study, when viewed partially, found that FOMO does not have a positive and significant influence on purchasing decisions. Meanwhile, Product Quality and Social Proof have a significant positive influence on Purchasing Decisions. And when viewed simultaneously, all independent variables together influence Purchasing Decisions.